2013
DOI: 10.5539/ass.v9n4p158
|View full text |Cite
|
Sign up to set email alerts
|

Examining Perceived Risk and Its Influence on Attitudes: A Study on Private Label Consumers in Turkey

Abstract: This study aims to examine perceived risk and its impact on consumers' attitudes towards private label brands. In order to achieve this aim, a field research was conducted on private label consumers in Turkey. 413 consumers attended the survey. According to the findings, the dimensions of the perceived risk towards private labels were determined as "financial risk", "physical risk", and "social risk". The perceived risk consisting of these dimensions has a negative influence on the attitudes towards private la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
1
16
1
Order By: Relevance
“…In addition, the perceived social risk construct scored a summated mean of 3.4834 out of 5 implying that the majority of the respondents perceived social risk as critical. This result is supported by the studies conducted by Arslan, Gecti and Zengin (2013) that revealed that perceived social risk is connected largely with buying behavior. Xue (2015), as well confirmed that consumer's buying behavior is influenced by perceived risks.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the perceived social risk construct scored a summated mean of 3.4834 out of 5 implying that the majority of the respondents perceived social risk as critical. This result is supported by the studies conducted by Arslan, Gecti and Zengin (2013) that revealed that perceived social risk is connected largely with buying behavior. Xue (2015), as well confirmed that consumer's buying behavior is influenced by perceived risks.…”
Section: Discussionsupporting
confidence: 65%
“…Section A of the questionnaire requested the biographical profile of the participant's respondents to provide their demographic profile. Section B of the questionnaire, which assessed perceived social risk, was adopted from Zhang, Tan, Xu and Tan (2012) as well as Arslan, Gecti and Zengin (2013). Section C of the questionnaire, measured buying behavior by employing a scale adopted from Kaul (2007) and Zhang et al (2012).…”
Section: Instrumentation and Collection Of Datamentioning
confidence: 99%
“…This result is different from previous findings (Semeijn et al, 2004;Mierer et al, 2006;Wu et al, 2011;Sheau-Fen et al, 2012;Arslan et al, 2013). This is because comparing to national brands, private labels in Vietnamese market are usually offered at competitive prices.…”
Section: Theoretical Model With Moderating Effect (Tested By Sem)contrasting
confidence: 56%
“…Semeijn et al (2004) early confirm the negative effect of perceived risk on consumer's evaluation toward private label products. Thereafter, recent research also come up with the same findings (Mierer, Martin, & Gutierrez, 2006;Wu et al, 2011;Sheau-Fen et al, 2012;Arslan et al, 2013).…”
Section: B Perceived Riskmentioning
confidence: 52%
See 1 more Smart Citation